Elementi upravljanja s stroški zdravil v Sloveniji - Kos, Mitja (Farmacevtski vestnik, 2015)
The aim of the article is to describe cost management elements of medicines from the perspective of health care payer in Slovenia. External reference pricing that is processed by JAZMP defines the maximum allowed price. Subsequently, ZZZS through the inclusion of medicine on the list negotiates a price lower than the maximum allowed price. Additionally, ZZZS manages medicine cost by limiting prescribing, generic substitution, therapeutic groups and risk sharing agreements.
Keywords: upravljanje s stroški zdravil; sistem zunanje primerjave cen; sistem notranje primerjave cen; omejitve predpisovanja; dogovori o deljenju tveganja